2006
DOI: 10.1007/s00005-006-0016-0
|View full text |Cite
|
Sign up to set email alerts
|

Elevated TGF-β1 concentration in bronchoalveolar lavage fluid from patients with primary lung cancer

Abstract: Our findings confirmed that TGF-beta takes part in the local response in the course of primary lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 29 publications
1
38
0
2
Order By: Relevance
“…We also found that TGF-β in BALF was higher in NSCLC patients than in healthy controls. That is also in line with other studies in which the highest level of the protein has been reported in lung cancer of advanced stage (Domagała-Kulawik et al 2006). Distinct differences in BALF content of TGF-β protein between NSCLC and BBS patients, make this protein potentially useful in initial differential diagnosis.…”
Section: Discussionsupporting
confidence: 91%
“…We also found that TGF-β in BALF was higher in NSCLC patients than in healthy controls. That is also in line with other studies in which the highest level of the protein has been reported in lung cancer of advanced stage (Domagała-Kulawik et al 2006). Distinct differences in BALF content of TGF-β protein between NSCLC and BBS patients, make this protein potentially useful in initial differential diagnosis.…”
Section: Discussionsupporting
confidence: 91%
“…TGFß1 regulates growth and proliferation of cells and may have a dual role in cancer (Tang et al 1999). This growth factor is involved in diVerent processes observed in malignancies, such as cellular proliferation, angiogenesis, immunological modulation, Wbroblast activation with remodeling of extracellular matrix and inXammation (Domagala-Kulawik et al 2006). TGFß1 inhibits the proliferation and induces the diVerentiation of normal bronchial epithelial cells (Elliott and Blobe 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation in COPD is characterized by prevalence of CD8 + lymphocytes, neutrophils, proinflammatory cytokines and a deficiency of regulatory lymphocytes [12]. Analysis involving the condition of immune system in patients with pulmonary carcinoma one must take into account history of cigarette smoking and potential diagnosis of COPD [15] .…”
Section: Analysis Of Immune System Cells In Lung Carcinomamentioning
confidence: 99%